Comparing of the efficacy of antacid and combination of antacid and H2RA on active nonvariceal upper gastrointestinal bleeding - Ali ERGİN and Kadir AKSÖZ and Günay ÖNDER and Uğur GÖNENÇ and Nafi YAZICIOĞLU and Belkıs ÜNSAL and Himmet KARACA and Sadun KOŞAY (Turkish Journal of Gastroenterology, 2020)
-